Fatimah Az Zahra Sermon in Developing the Character of Courage in Female Students at School - Aisyah Salsabila Arsa; Akmaliyah Akmaliyah; Mohammad Rosyid Ridho; Iis Nurasiah (Vidya Karya, 2026)
This study aims to analyze the representation of Fatimah Az Zahra's courage in the Fadakiyah Sermon through the perspective of Pierre Bourdieu's sociology of literature, and to examine its relevance in fostering the character of courage among female students at SDIT Aisyiyah. The method used is a descriptive qualitative method with a literature review, using primary data in the form of the Fadakiyah Sermon text and the biography of Fatimah Az-Zahra, as well as secondary data from bibliometric analyses of various related journals. The results of the study indicate that Fatimah Az-Zahra's courage is a symbolic practice formed from habitus in the political arena. This courage is realized through the use of symbolic capital (status as the daughter of the Prophet Muhammad), social capital (relationships with the people of Medina), cultural capital (mastery of the Qur'an), and economic capital (inheritance rights of the Prophet's family) in opposing injustice related to the land of Fadak. The analysis also shows a relationship between the application of sermon values and the development of courage in female students.  This research suggests that the sermon method may affect the development of courage among female students. This is a recommendation to conduct research on implementing this method in the world of language and education.